Solo Extracorporeal Shock Wave Lithotripsy for Management of Upper Ureteral Calculi With Hydronephrosis - Wadhera, Sushant; Mathur, Rajkumar K; Odiya, Sudershan; Raikwar, Ram Sharan; Girish, Govindaiyah (Urology Journal, 2008)
Introduction: The aim of this study was to evaluate extracorporeal shock wave lithotripsy (SWL) outcomes as a solo therapy in patients with upper ureteral calculi and varying degrees of hydronephrosis. Materials and Methods: Eighty patients with upper ureteral calculi and a body mass index between 19.5 kg/m2 and 22.5 kg/m2 were included. They were categorized into 4 groups according to the severity of hydronephrosis as seen on ultrasonography and intravenous urography: group 1, no dilatation; group 2, mild dilatation; group 3, moderate dilatation; and group 4, severe dilatation of the pyelocaliceal system. The size of calculi, time to calculus clearance, success rate of solo SWL, and the need for additional therapeutic methods were recorded and compared between the four groups of patients. Results: The median size of the calculi was 13.5 mm, and the mean time to calculus clearance was 56.0 Â± 24.2 days. In 71.3% of the patients, solo SWL was successful in the treatment of the calculi. Twenty-three patients required other therapies including double-J stenting, ureteroscopy, and nephrolithotomy. The patients without hydronephrosis and those with severe hydronephrosis (groups 1 and 4) showed a significant difference in the days to clearance of the calculus (mean, 31.7 days versus 85.6 days; P < .001). Conclusion: Patients with upper ureteral calculi and mild hydronephrosis can be effectively treated with solo SWL therapy. In those with moderate hydronephrosis, clearance takes longer or requires secondary interventions. In patients with severe hydronephrosis, we recommend alternative/adjunctive procedures.